1997
DOI: 10.1093/ortho/24.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the changes in facial profile after orthodontic treatment, with and without extractions.

Abstract: A study was made of 31 patients with Angle Class II malocclusion. Fifteen patients did not undergo extraction of teeth (Group A), while 16 underwent extractions of four premolars (Group B). Data was obtained from the corresponding lateral radiographs of the head taken both before and after orthodontic treatment. The main aim of the study was to compare the response of the soft and hard tissues of the facial profile in Class II malocclusion treated with the extraction of four premolars and the response of borde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 30 publications
1
30
0
9
Order By: Relevance
“…In this study, this increase was greater than the expected being corroborated by some authors that reported similar results in literature. 4,7,23 On the maxillomandibular relation, there was a significant alteration of the anteroposterior skeletal discrepancy, shown by the reduction of angle ANB (Table 1). This alteration was expected because the orthodontic treatment aimed the correction of Class II malocclusion and of the overjet initially increased by upper incisors retraction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, this increase was greater than the expected being corroborated by some authors that reported similar results in literature. 4,7,23 On the maxillomandibular relation, there was a significant alteration of the anteroposterior skeletal discrepancy, shown by the reduction of angle ANB (Table 1). This alteration was expected because the orthodontic treatment aimed the correction of Class II malocclusion and of the overjet initially increased by upper incisors retraction.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Several authors did not find significant differences on the alterations of soft tissue between groups treated with extraction of four premolars and without extractions 7,30 while other authors observed a tissue profile retrusion. 1, 3,4 Considering that a retraction of upper incisors necessarily imply in a retrusion of the upper lip, 30 it is known that the muscle-skeletal-functional complex of the upper lip contributes for the variability observed on alterations of upper lip with the treatment protocol with premolars extractions. 29 In this work the nasolabial angle did not present statistically significant alteration (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not statistically significant, greater changes in the position of the labrale inferiorus were observed in extraction cases than in nonextraction cases. It has been previously shown 9,10,21 that the extraction cases become significantly more retrusive than nonextraction cases based on measurements determined by the E-line and B-Line. In contrast, Janson et al 22 showed no significant differences between nonextraction and maxillary first premolar extraction cases using the Steiner's S1-line and the Rickett's E-line; they did find significant differences based on the Burstone's B-line.…”
Section: Discussionmentioning
confidence: 99%
“…The Hline and B-line have been used to determine the amount of protrusion or retrusion of the lips that occurs during treatment. 10 More recently Stalpers et al 11 used the E-line to measure the changes that occur in lower lip position with the extraction of maxillary first permanent molars in Class II division I patients, and Zablocki et al 12 relied upon the E-line to evaluate lower lip changes produced with a transpalatal ach during the treatment of extraction cases. Pecora et al 13 used the E-line to measure the changes in the lip position that occur between late adolescence, mid-adulthood, and late adulthood.…”
Section: Introductionmentioning
confidence: 99%